2010
DOI: 10.1093/intqhc/mzq001
|View full text |Cite
|
Sign up to set email alerts
|

The health implications of apologizing after an adverse event

Abstract: Australia is working towards a National Open Disclosure Standard in which all adverse incidents are disclosed to patients in all health-care facilities in the country. Among the many good reasons for this approach, one that has not attracted attention is the possibility that disclosure of an adverse incident may moderate its impact on the recovery and general health of patients. In this article, we discuss this perspective with reference to relevant psychological and physiological literature. In the absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…Allan and McKillop (2010) suggested that the increased likelihood of forgiveness serves as a strong rationale for a medical standard that requires adverse medical events to be disclosed. Allan and McKillop (2010) suggested that the increased likelihood of forgiveness serves as a strong rationale for a medical standard that requires adverse medical events to be disclosed.…”
Section: Forgiving (Or Receiving Forgiveness From) Whom? Self Othersmentioning
confidence: 99%
“…Allan and McKillop (2010) suggested that the increased likelihood of forgiveness serves as a strong rationale for a medical standard that requires adverse medical events to be disclosed. Allan and McKillop (2010) suggested that the increased likelihood of forgiveness serves as a strong rationale for a medical standard that requires adverse medical events to be disclosed.…”
Section: Forgiving (Or Receiving Forgiveness From) Whom? Self Othersmentioning
confidence: 99%
“…While an apology can be defined in various ways, certain key elements have been identified in the literature. These include acknowledging that harm has occurred, accepting responsibility for causing the harm, expressing regret, and taking action to remedy the harm and prevent future occurrences (ACSQHC 2012; Allan and McKillop 2010).…”
Section: The Role Of Apologiesmentioning
confidence: 99%
“…They can cause complications, stress, anxiety, the loss of a patient's life [12], health [13] and in the best case scenario -can contribute to financial losses [14] and the loss of hospital reputation [15]. They can also reinforce a sense of threat, of helplessness and can affect the general quality of life [16,17].…”
Section: Discussionmentioning
confidence: 99%